2013
DOI: 10.1159/000346485
|View full text |Cite
|
Sign up to set email alerts
|

Home Artificial Nutrition in Switzerland: An Epidemiological Survey from 2005 to 2009

Abstract: Background and Aims: Home artificial nutrition (HAN), including oral nutritional supplements (ONS) and enteral (HEN) and parenteral (HPN) nutrition, is an established, important treatment for malnourished patients. The aim of this study was to analyze the epidemiological data of patients on HAN in Switzerland. Methods: This retrospective study recorded all new cases of HAN in Switzerland from January 2005 to December 2009. Results: A total of 12,917 cases were recorded: 6,731 (52%) males and 6,186 (48%) female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 18 publications
3
15
0
Order By: Relevance
“…Our results are similar to those of HPN programs in other countries. Oncology patients represented the largest percentage of HPN patients in studies from Spain (49.5%), 5 Switzerland (57.4%), 13 and the United States (42%) 14 . The increasing number of cancer patients in the HPN programs might contribute to the more frequent use of PICC in some centers where chemotherapy might be delivered via this route.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are similar to those of HPN programs in other countries. Oncology patients represented the largest percentage of HPN patients in studies from Spain (49.5%), 5 Switzerland (57.4%), 13 and the United States (42%) 14 . The increasing number of cancer patients in the HPN programs might contribute to the more frequent use of PICC in some centers where chemotherapy might be delivered via this route.…”
Section: Discussionmentioning
confidence: 99%
“…Wide variation exists in the data reported regarding the primary medical condition of patients requiring HPN. In many countries, the largest diagnostic category of HPN recipients consists of patients with active cancer, whereas Crohn's disease, short bowel syndrome, and surgical complications are more common reasons for HPN in others 5 . ‐ 8 A downward trend in the use of HPN for Crohn's disease may reflect advances in the treatment of the disease, but more research is needed to confirm this premise 5 …”
Section: Question 10: Which Patients Are Appropriate For Home Pn Thermentioning
confidence: 99%
“…The proportion of HPN patients with oncological tumors has increased over the past years in Europe [28] . Previous Swiss data about the indications for home artificial nutrition demonstrated that neoplasms were the most frequent underlying disease (51%), diseases of the digestive system on the second place (10.4%) and diseases of the nervous system in third place (9.6%) [8] . In our study, there were no patients with underlying neurological disorders.…”
Section: Discussionmentioning
confidence: 96%
“…The most common indications for long-term HPN in Europe are Crohn's disease, mesenteric vascular disease, cancer and radiation enteritis [7] . Other more recent studies confirm that malignancy is the single most common indication for HPN [8,9] .…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation